2020
DOI: 10.2147/mder.s240343
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of Endoscopic Stapler Selection on Bleeding at the Vascular Stump in Pulmonary Artery Transection</p>

Abstract: Objective: To assess bleeding following transection of the pulmonary artery with powered and manual endoscopic staplers. Methods: Cases of video-assisted and open-chest thoracic surgical procedures for non-small cell lung cancer at Ishikawa Prefectural Central Hospital were reviewed between 2012 and 2018. Three stapler groups were assessed: Group 1-Ethicon ECHELON FLEX TM Powered Vascular Stapler (PVS), Group 2-Medtronic Endo-GIA TM iDrive TM powered stapler, Group 3-Ethicon and Medtronic manual staplers. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In any case, high compression on delicate vessels can cause damage away from the closed ends of the divided structure leading one group of investigators to cite stapler gap distance as an important consideration during pulmonary stapling. 2 In any case, this report underscores the need to surveil for errant, partially embedded, and malformed staples while operating. To the extent that small vessel division might increase this problem because there is less vascular wall for staple incorporation, we might consider greater use of Surgeons need to appreciate the general and device-specific mechanisms by which endomechanical staplers cause vascular injuries.…”
mentioning
confidence: 74%
“…In any case, high compression on delicate vessels can cause damage away from the closed ends of the divided structure leading one group of investigators to cite stapler gap distance as an important consideration during pulmonary stapling. 2 In any case, this report underscores the need to surveil for errant, partially embedded, and malformed staples while operating. To the extent that small vessel division might increase this problem because there is less vascular wall for staple incorporation, we might consider greater use of Surgeons need to appreciate the general and device-specific mechanisms by which endomechanical staplers cause vascular injuries.…”
mentioning
confidence: 74%
“…The superior clinical effects of powered staplers over manual staplers in VATS lobectomy for lung cancer have been widely presented [4][5][6][7]. To further compare the two types of staplers, this study uses CMA to assess the economic impact of utilizing a powered stapler in VATS lobectomy for lung cancer in a Chinese tertiary hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a powered stapler was developed to address this limitation by using a motor to power both the staple firing and the cutting action of the blade. A powered stapler can reduce movement at the distal tip by 88% when compared to a manual stapler [4]. In addition, the use of a powered stapler can prevent the operating surgeon's intraoperative hand tremors thereby minimizing tissue damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Japan, presented a case series that showed potential benefits of lower bleeding at the vascular stump in pulmonary artery transection associated with the use of Ethicon's ECHELON FLEX™ Powered Vascular Stapler as compared with Medtronic's iDrive TM powered stapler. 9 However, no other comparative assessment between powered staplers is available to the best of our knowledge at the time of this writing. Therefore, we conducted this retrospective study to assess the comparative real-world risk of hemostasis-related complications and other outcomes associated with the use of the powered staplers GST and SIG among patients undergoing laparoscopic sleeve gastrectomy for obesity.…”
Section: Introductionmentioning
confidence: 99%